2020
DOI: 10.15252/embj.2020105380
|View full text |Cite
|
Sign up to set email alerts
|

Local externalization of phosphatidylserine mediates developmental synaptic pruning by microglia

Abstract: Neuronal circuit assembly requires the fine balance between synapse formation and elimination. Microglia, through the elimination of supernumerary synapses, have an established role in this process. While the microglial receptor TREM 2 and the soluble complement proteins C1q and C3 are recognized as key players, the neuronal molecular components that specify synapses to be eliminated are still undefined. Here, we show that exposed phosphatidylserine ( PS ) represen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
191
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 262 publications
(219 citation statements)
references
References 86 publications
6
191
0
Order By: Relevance
“…Exposed PS have been shown in the cortex of adult mice in isolated synaptosomes that are also tagged by C1q (Györffy et al, 2018 ) and have also been observed in vivo at presynaptic inputs in the hippocampus and in the dLGN of developing mice (Scott-Hewitt et al, 2020 ). During development, deletion of C1q results in increased PS-labeled presynaptic inputs and decreased microglial engulfment of PS-labeled elements (Scott-Hewitt et al, 2020 ), implicating C1q in the elimination of PS-labeled synapses. It is likely that in this context, PS-labeled elements are engulfed by microglia via the phagocytic receptor TREM2 since, in hippocampal neuron and microglia co-cultures, synapse elimination can be partially prevented by deleting TREM2 on microglia (Scott-Hewitt et al, 2020 ).…”
Section: Complement In Msmentioning
confidence: 98%
See 3 more Smart Citations
“…Exposed PS have been shown in the cortex of adult mice in isolated synaptosomes that are also tagged by C1q (Györffy et al, 2018 ) and have also been observed in vivo at presynaptic inputs in the hippocampus and in the dLGN of developing mice (Scott-Hewitt et al, 2020 ). During development, deletion of C1q results in increased PS-labeled presynaptic inputs and decreased microglial engulfment of PS-labeled elements (Scott-Hewitt et al, 2020 ), implicating C1q in the elimination of PS-labeled synapses. It is likely that in this context, PS-labeled elements are engulfed by microglia via the phagocytic receptor TREM2 since, in hippocampal neuron and microglia co-cultures, synapse elimination can be partially prevented by deleting TREM2 on microglia (Scott-Hewitt et al, 2020 ).…”
Section: Complement In Msmentioning
confidence: 98%
“…Antibodies are the obvious candidate, but deposits of immunoglobulins were not detected in the MS hippocampus. An alternative target of C1q is an apoptotic signal on the surface of dead or dying cells, such as the previously identified ceramide transporter protein (Bode et al, 2014 ) or the externalization of phosphatidylserine (PS; Scott-Hewitt et al, 2020 ). Exposed PS have been shown in the cortex of adult mice in isolated synaptosomes that are also tagged by C1q (Györffy et al, 2018 ) and have also been observed in vivo at presynaptic inputs in the hippocampus and in the dLGN of developing mice (Scott-Hewitt et al, 2020 ).…”
Section: Complement In Msmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous work in other pathological contexts suggest candidate factors, including chemokines such as CX3CL1 ( Lee et al, 2014 ) and CCL2/3 ( Welikovitch et al, 2020 ), factors released in response to oxidative stress ( Wilson et al, 2018 ), myelin debris, or extracellular ATP ( Cserép et al, 2020 ; Davalos et al, 2005 ; Neumann et al, 2009 ). Factors involved in microglia-neuron interactions during development, including complement or phosphatidylserine (PS) exposure ( Scott-Hewitt et al, 2020 ) could also play a role in the interactions we observe here in early AD. Recently, microglial interactions with neuronal soma have been linked to the level of neuronal activity, supported by TRPV1-expressing neurons activated by capsaicin exhibiting increased soma contacts by microglia ( Hughes and Appel, 2020 ).…”
Section: Discussionmentioning
confidence: 95%